Reduction of chronic malnutrition for infants in Bogotá, Colombia - Paula Andrea Castro Prieto; Kenny Margarita Trujillo Ramírez; Sergio Moreno; Juan Sebastián Holguín; Diana María Pineda; Simón Tomasi; Andrea Ramirez Varela (BMC, 2021)
Abstract Background According to the 2015 National Survey of the Nutritional Situation in Colombia the prevalence of stunting in children under 5 years of age was 10.8%. In terms of region, Bogotá, presented the highest prevalence rate (13%), a figure that exceeded national records. With the collaboration of local and national government, and nongovernmental it was decided to develop a pilot study involving a public health intervention with residents of Bogotá under 1 year of age with nutritional classification by anthropometry compatible with stunting risk or stunting. Methods Pre-experimental, before and after study that sought to determine the magnitude of the change in nutritional status through a 10 months public health nutrition intervention in children under one-year-old residing in 3 prioritized territories of Bogotá. Results The intervention comprised 1126 children living in the following territories in Bogotá: Kennedy, San Cristóbal, and Engativá. A total of 43.3% children presented delay in height for age, and 56.7% presented risk of short stature. In the final measurement, data were obtained from 686 children, identifying that 17% of the children progressed from stunting to a stunting risk and that 4.5% recovered their growth trajectory, achieving an adequate length for their age. Conclusion That children classified as at risk or stunting at the beginning of the intervention showed an increased probability of approaching or being in the appropriate growth trajectory according to the length-for-age indicator after the intervention.